Anesthesia for Nonobstetric Surgery During Pregnancy in a Tertiary Referral Center: A 16-Year Retrospective, Matched Case-Control, Cohort Study. Issue 2 (June 2020) - Devroe, S.; Bleeset, T.; Van de Velde, M.; Verbrugge, L.; De Buck, F.; Deprest, J.; Devlieger, R.; Rexa, S.
Abstract : ( Int J Obstet Anesth . 2019;39:74–81) Nonobstetric operative interventions during pregnancy are fairly uncommon, but can increase the risk of preterm delivery, low birth weight, and cesarean delivery. There has been limited research conducted on the pregnancy outcomes of women who undergo nonobstetric surgical procedures. These investigators, therefore, conducted this retrospective analysis to compare pregnancy outcomes in parturients who underwent nonobstetric surgical procedures to their hospital's entire obstetric patient population as well as to a matched case-control cohort based on similar demographics.